2005
DOI: 10.1016/j.jacc.2004.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Better outcome after pediatric defibrillation dosage than adult dosage in a swine model of pediatric ventricular fibrillation

Abstract: In this model, pediatric shocks resulted in superior outcome compared with adult shocks. These data suggest that adult defibrillation dosing may be harmful to pediatric patients with VF and support the use of attenuating electrodes with adult biphasic AEDs to defibrillate children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 15 publications
1
30
1
4
Order By: Relevance
“…(5) Biphasic shocks of high energy levels (360 J) are potentially harmful if used in low-weight small animals, as demonstrated in animal studies, (6,7) but not in humans. (8,9) Based on these fi ndings, it is reasonable to recommend that, based on the type of waveform used and the manufacturer's recommendations for the model of defi brillator, energy levels in the range of 120-200 J can be used to deliver the fi rst shock for VF.…”
Section: Defi Brillation Energymentioning
confidence: 99%
“…(5) Biphasic shocks of high energy levels (360 J) are potentially harmful if used in low-weight small animals, as demonstrated in animal studies, (6,7) but not in humans. (8,9) Based on these fi ndings, it is reasonable to recommend that, based on the type of waveform used and the manufacturer's recommendations for the model of defi brillator, energy levels in the range of 120-200 J can be used to deliver the fi rst shock for VF.…”
Section: Defi Brillation Energymentioning
confidence: 99%
“…Der AED soll mit einem Leistungsminderer ausgestattet sein, der die abgegebene Energie auf eine für Kinder im Alter von 1-8 Jahren besser geeignete Dosis reduziert (50-75 J; [317,323] …”
Section: Pad-/paddlegröße Für Die Defibrillationunclassified
“…A study by Berg et al 44 in 2003 compared a single escalating energy sequence (50,75, and 86 J) of an attenuated adult-dose biphasic shock, nonattenuated adult-dose biphasic shock, and weight-based monophasic shock for piglets with prolonged VF. The attenuated and monophasic dosages were delivered via pediatric pads and the nonattenuated dose was delivered via adult pads.…”
Section: Aed Energy and Waveform Safety And Efficacymentioning
confidence: 99%
“…In addition, the study indicated that the adult biphasic AED, although not as good as the attenuated dosage, was superior in outcome and LV ejection fraction to the weight-based monophasic AED. In another study, Berg et al 45 showed that escalating attenuated adult-dosage biphasic shocks are more effective and have fewer adverse outcomes than standard escalating adult-dosage biphasic shocks. Although the attenuated dosage was more effective and had fewer adverse effects on the myocardium, the adult escalatingdosage biphasic shocks also were effective in terminating VF in this piglet model of pediatric VF.…”
Section: Aed Energy and Waveform Safety And Efficacymentioning
confidence: 99%
See 1 more Smart Citation